Penatalaksanaan Holistik Ulkus Kaki Diabetik Melalui Pendekatan Kedokteran Keluarga - Ananda Christie Angelin; Reni Zuraida (CV. Jasa Sukses Abadi, 2022)
Diabetes mellitus (DM) has reached epidemic proportions worldwide, Indonesia is the sixth ranked country in the world. Diabetes with complications is the third highest cause of death in Indonesia. This study applies a holistic and comprehensive family doctor service by identifying risk factors, clinical problems and patient management based on Evidence Based Medicine with a patient centered approach and a family approach in cases of diabetes with complications of diabetic foot ulcers. Primary data were obtained through history taking (autoanamnesis from the patient and alloanamnesis from the patient's family), physical examination and home visits. Patient Mrs. K, 56 years old, was diagnosed with Diabetic Foot Ulcers and Type 2 Diabetes Mellitus. The patient has limited support and knowledge of the family about the patient's disease and its complications as well as the pattern of curative treatment. Holistic and comprehensive management of Mrs. K has been carried out to increase the knowledge of patients and families about DM with complications.